GAMBARAN PENGETAHUAN IBU NIFAS TENTANG METODE KANGURU YANG MEMILIKI BAYI BERAT LAHIR RENDAH DI RSKD IBU DAN ANAK SITI FATIMAH MAKASSAR - Hasnidar (Jurnal Suara Kesehatan, 2015)
ABSTRACT; Knowledge of puerperal women about the kangaroo method is very important because with the knowledge puerperal women will know the kangaroo method. It also can reduce the occurrence of hypothermia in infants. This type of research is descriptive, which aims to reveal the puerperal women knowledge about methods of kangaroos in RSKIA Siti Fatimah Makassar. A population of 121 puerperal women who had low birth weight babies. Sample of 30 people who had a low birth weight babies who do kangaroo method in this research with accidental sampling technique. The results showed 30 puerperal women, postpartum mothers knowledge about the understanding of the kangaroo method know as much as 10 people (66.7%) and who do not know 20 people (33.3%), the benefits of kangaroo method that out of 15 people (50% ) and who do not know 15 people (50%), profit kangaroo method know as much as 9 people (30%) and do not know as much as 21 people (70%), procedures for the kangaroo method know as much as 5 people (16.7%) and do not know 25 people (83.3%).